Isolation and Characterization of a Novel Recombinant Classical Pseudorabies Virus in the Context of the Variant Strains Pandemic in China - Zhengmin Lian; Panrao Liu; Zhenbang Zhu; Zhe Sun; Xiuling Yu; Junhua Deng; Ruichao Li; Xiangdong Li; Kegong Tian (Viruses, 2023)
Pseudorabies virus (PRV) variants were discovered in immunized pigs in Northern China and have become the dominant strains since 2011, which caused huge economic losses. In this study, a classical PRV strain was successfully isolated in a PRV gE positive swine farm. The complete genome sequence was obtained using a high-throughput sequencing method and the virus was named JS-2020. The nucleotide homology analysis and phylogenetic tree based on complete genome sequences or gC gene showed that the JS-2020 strain was relatively close to the classical Ea strain in genotype II clade. However, a large number of amino acid variations occurred in the JS-2020 strain compared with the Ea strain, including multiple immunogenic and virulence-related genes. In particular, the gE protein of JS-2020 was similar to earlier Chinese PRV strains without Aspartate insertion. However, the amino acid variations analysis based on major immunogenic and virulence-related genes showed that the JS-2020 strain was not only homologous with earlier PRV strains, but also with strains isolated in recent years. Moreover, the JS-2020 strain was identified as a recombinant between the GXGG-2016 and HLJ-2013 strains. The pathogenicity analysis proved that the PRV JS-2020 strain has typical neurogenic infections and a strong pathogenicity in mice. Together, a novel recombinant classical strain was isolated and characterized in the context of the PRV variant pandemic in China. This study provided some valuable information for the study of the evolution of PRV in China.